Technocrats on the Firing Line - Halvorson, Raundi (Tufts Archival Research Center, 2005)
Volume 7, Issue 2. Summer Brazil experienced near-incredible growth during the late 1960s and early 1970s, but poor comprehensive planning combined with the worldwide recession have resulted in huge outstanding debt for the largest Latin American nation. In this article, Raundi Halvorson, who has lived and worked in Brazil, outlines in stark and almost startling detail the immensity of the economic and social difficulties Brazil is experiencing. She vividly describes the crucial planning choices (and errors) made by the Brazilian technocrats and offers potential governmental options based on economic realities, the Brazilians' wants and needs, and the inability or unwillingness of the current technocrats to both control inflation and push for greater social equity.